IMPLEMENTASI KEBIJAKAN PERIZINAN PERDAGANGAN (STUDI PADA UMKM WARUNG KOPI DI KECAMATAN WIYUNG, KOTA SURABAYA) - Mu'amar Khadafi Fachrudin; Suci Megawati (Universitas Negeri Surabaya, 2022)
The existence of coffee shops in Surabaya is now increasingly spreading in various areas which has now become a problem in the administrative compliance of SIUP management. So that there is a need for government efforts to bring order to business actors in obeying the administration. Surabaya Mayor Regulation N0.41/2021 concerning business licensing, non-business licensing and non-licensing services. With this regulation, the Surabaya city government issued a policy for every MSME business actor, coffee shops, cafes and coffee shops to have a SIUP. After the issuance of the policy, there are still many MSME business actors who have not pocketed SIUP. Thus, it is necessary to know how to implement the Trade Licensing Policy for coffee shop MSME business actors in Wiyung sub-district, Surabaya city. In the process of this research using descriptive qualitative research with techniques to collect data from observations and interviews with DPM-PTSP Surabaya City and District Wiyung Surabaya. From the results of research conducted by researchers, it is stated that from The Accuracy of The Policies Implemented, it can run well in line with the regulations issued by the Surabaya city government that business actors who are non-KTP Surabaya can manage SIUP. The accuracy of the implementation is not optimal because there are still business actors who have not pocketed SIUP. Target accuracy is also less than optimal because there are still business actors who have minimal technological knowledge in managing SIUP in the Online Single Submission (OSS) System online. Environmental Accuracy is also going well from the internal point of view of the policy implementer, but from the external point of view it still looks bad, namely the lack of contribution from business actors in implementing the mandatory SIUP. Keywords: Implementation, Trade Permits, Micro, Small, and Medium Enterprises.